Wave Propagation in a Pre-Stressed Reinforced Composite - Demiray, H. (Engineering Transactions, 1976)
In this study, a small time dependent displacement field is superimposed on an initial large static deformation, for a reinforced composite, and the linearized field equations and associated boundary conditions are obtained. Propagation of harmonic waves in such a composite medium is studied and various special cases are discussed. From the condition of propagation some criteria for the stability of equlibrium configuration are deducé.